2005
DOI: 10.1007/s11661-005-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reflow and thermal aging on the shear strength and fracture behavior of Sn-3.5Ag solder/Cu joints

Abstract: The mechanical behavior of Sn-rich solder/Cu joints is highly sensitive to processing variables such as solder reflow time, cooling rate, and subsequent thermal aging. In this article, we focus on the lap shear behavior of Sn-3.5Ag/Cu joints as a function of solder yield strength and intermetallic thickness. Experimental results showed that the shear strength of the solder joints is primarily controlled by the mechanical properties of the solder, and not the intermetallic thickness. The thickness of intermetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(70 citation statements)
references
References 37 publications
8
61
0
Order By: Relevance
“…The joint was assembled with the aid of a reflow fixture, to minimize misalignment and maintain a consistent joint solder thickness of approximately 500 mm. 25 The entire assembly was heated on a hot plate and held at 120°C for 20 min. to allow excess flux to vaporize.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…The joint was assembled with the aid of a reflow fixture, to minimize misalignment and maintain a consistent joint solder thickness of approximately 500 mm. 25 The entire assembly was heated on a hot plate and held at 120°C for 20 min. to allow excess flux to vaporize.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…4,12,15 These strain concentrations arise due to misfit strains induced via elastic-plastic mismatch between the solder and the IMC layer. 10,12,13 In addition, strain localization within the solder immediately adjacent to and parallel to the interface can cause stress concentrations in the scallops, enhancing the propensity for IMC fracture.…”
Section: Considerations For Defining Effective Imc Thicknessmentioning
confidence: 99%
“…Deng et al focused on the lap shear behavior of Sn-3.5Ag/Cu joints as a function of solder yield strength and intermetallic thickness. eir experimental results showed that the shear strength of the solder joints is primarily controlled by the mechanical properties of the solder and not by the intermetallic thickness [14]. Lee and Lee investigated composite lead-free solders fabricated by adding between 0.5 and 3 wt.% of Ni particles in situ to Sn-3.5 wt.% Ag lead-free solder and found that the single lap shear strength of the joints increases with increasing Ni addition in the as-reflowed condition but decreases with increasing storage time in the aged specimens [15].…”
Section: Introductionmentioning
confidence: 99%